Strategi Pemasaran Inovatif untuk Mempromosikan Rumah Adat Dayak Kalimantan Barat - Ichsan, Imron Rosyadi (Syntax Literate, 2025)
The traditional Dayak house of West Kalimantan is an inseparable part of the rich and valuable cultural heritage. As one of the unique and beautiful forms of traditional traditional houses, the Dayak traditional house is not only a symbol of the cultural identity of its people, but also a potential tourist attraction. The modernization that continues to develop in West Kalimantan has a major influence on social and cultural change. Social and cultural changes that occur in West Kalimantan indicate competition between local culture and global culture. Tourist visits to the Radakng Sahapm house in 2018 only numbered 2,587 local tourists and 20 foreign tourists. This shows that there is a lack of interest from tourists to visit cultural tourism such as the Radakng House, so a strategy is needed to market cultural-based tourism. The research method used is the Qualitative method. Data was obtained through interviews and literature studies. The results of the study discuss the current promotion of Radakng House tourism, obstacles, and innovative marketing strategies for Radakng House. In formulating a strategy, it is necessary to ensure the goals to be achieved, the means that can be used and the steps that must be taken. In addition, it is strengthened through SWOT Analysis.